The Covid-19 Pandemic Impact on Tourism Business in Kuta Beach Bali: A Naturalistic Qualitative Study - Wulandari, I Gusti Ayu Athina; Mahagangga, I Gusti Agung Oka (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
The purpose of this research is to analyse the COVID-19 pandemic impacts on tourism in Kuta beach, Badung regency, Bali Province. This is a naturalistic qualitative inquiry with  the purposive sampling method used to the informants. As the key instruments are the researchers through in-depth interviews, observations, and literature studies. The qualitative data analysis used descriptive interpretative was applied to understand the tourism condition in Kuta beach due to the COVID-19 pandemic. The findings show the pandemic affected tourist activities in Kuta Beach, including businesses, such as surfboard training and rental, restaurants, and accommodation.  The pandemic impacted income declines, tourism businesses closure, and layoffs Business actors expect the pandemic to end soon to increase foreign tourists to Bali. Even thought there are domestic tourists who visited, but feel not effective to recovery their business. Insights from this research also finding the local government with support from the central government in Jakarta try replaced tourism as the leading sector with agriculture. Hence, appears the government not contribute to recovery yet and doubt to make decision.